(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2016)
The meaningful content of the development program of the multifunctional territories (MFT) in Tatarbunar’s district of the Odessa region is substantiated in the article. The essence of the program as a document providing the implementation of strategies aimed at effective, integrated use of natural resources, economic and social potential of the district to enhance tourism activities, and taking into account the restrictive environmental factor, namely the functioning of the existing protected areas and functional zoning, is defined. The goals of the program of multifunctional territories are established. The content of the main sub-programs: «The Use and Protection of Tourist Potential’s Elements of MFT», «Socio-Economic Ensure of the District’s MFT Development», «Legal and Organizational Maintenance and Management of the Program» are grounded. Proposals to establish a tourism corporation in Tatarbunar’s district of Odessa region are worked out.